Comparative Study of Total Phenolics and Antioxidants in ASTRAGLUS STOCKSII by using Methanol, Ethanol and Acetone and to Evaluate its Anti-Inflammatory Activity - Arshad, Iqra; Ayub Kakar, Muhammad; ur-Rehman Kakar, Attiq-; Hassan Kakar, Noor; Khanam, Saeeda; Kamal, Rehana; Muhammad, Atta (Al-Nahrain Journal of Science, 2021)
Astragalus Stocksii a local flowering plant found in Hana Valley, Quetta Pakistan, used as home medicinal plant form many years. It is an encouraging source of bioactive compounds and has been conventionally manipulated for the coverage of several diseases. The present study based on the evaluation of phenolics, antioxidants and anti-inflammatory activities of Astragalus Stocksii by using three different solvents, i.e.; acetone, ethanol and methanol. The results showed that extraction yield depends upon the type of the solvents used for extraction. Among these, extraction in methanol has the highest phenolic contents (10.086±0.08mg CE/g DW), total antioxidant capacity (TAC, IC50 =14.50±0.01 µg/mL, phospho-molibdenum method, IC50 = 66.62± 0.03 µg/mL by DPPH method) and high anti-inflammatory activity (IC50 =75.0 ±2.5 µg/mL, oxidative burst assay). These results indicate that methanol is the best solvent for extraction of phenolic and antioxidants in Astragalus Stocksii. The high results of anti-inflammatoryfor Astragalus Stocksii suggests its use in pharmaceutical and nutraceutical industries.